187RE-187OS evidence for crustal lenses of Svecofennian age within the Mylonite Zone, SW sweden - Scherstn, Anders ; 0000-0002-2105-6172 (GFF, 2002)
Re and Os concentrations and isotopic composition were analysed in four ultramafic cumulates from the Kedum tectonic lens within the Mylonite Zone, SW Sweden. An 1887±36 Ma isochron is obtained for six samples and interpreted to date the Kedum body. This is significantly older than the -1600-1700 Ma surrounding crust and the first rocks of Svecofennian age west of the Trans Scandinavian Igneous Belt. The initial gOs of 15.7±4.0 indicates contribution from a radiogenic source such as old crust.
Keywords: Baltic shield; Dating; Re-Os; Southwest scandinavian domain; Svecofennian; Ultramafic